A Standard Operating Procedure (SOP) for: an in-situ under-ice hyperspectral imaging and photogrammetric system. A laboratory based hyperspectral imaging sea ice core scanner - Cimoli, E; Lucieer, V (Antarctic Gateway Partnership, 2020)
This Standard Operating Procedural (SOP) report outlines the design specification and operatorial procedure for users of the IMAS and Antarctic Gateway Partnership under-ice sliding hyperspectral imaging and photogrammetric system and its complementary ice core scanner. The SOP provides details on all elements of the equipment required for data collection and extends to include procedures for pre-survey preparation, field operations and post-survey data processing using the 2019 custom designed system.It is important to note that this optical based system was specifically designed for mapping fine-scale biophysical properties of sea-ice at the ice water interface (e.g., algal biomass and sea ice topography). However, capabilities to adapt the system for scanning different targets (e.g., benthos) are envisaged and are feasible with further minor modifications to V1 of this SOP.It is intended that as upgrades to the system will occur in the future and that this SOP will be updated accordingly.